1998
DOI: 10.1111/j.1365-8711.1998.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field strengths in the hotspots of 3C 33 and 111

Abstract: A B S T R A C TWe report on ROSAT HRI observations of the nearby powerful radio galaxies 3C 33 and 111, which both have detected optical hotspots. We find nuclear X-ray sources in both objects, but no X-ray emission from the hotspots. This confirms the presence of a high-energy cut-off in the spectrum of synchrotron-emitting electrons. Since these electrons necessarily scatter the synchrotron photons by the inverse Compton process, our upper limits on the X-ray fluxes of the hotspots allow us to set lower limi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 28 publications
2
80
0
Order By: Relevance
“…Since the appearance of earlier work aimed explicitly at detecting hot spots (Harris et al 2000;Hardcastle et al 2001a;H02;Brunetti et al 2002), a number of hot spots have been detected in Chandra observations of FR II radio galaxies and quasars made for other purposes (e.g., Donahue et al 2003;. This has motivated us to collate all existing data on the hot spots of 3C radio sources from the Chandra archive and analyze them in a systematic way, with the aim of determining trends and testing models.…”
Section: Introductionmentioning
confidence: 99%
“…Since the appearance of earlier work aimed explicitly at detecting hot spots (Harris et al 2000;Hardcastle et al 2001a;H02;Brunetti et al 2002), a number of hot spots have been detected in Chandra observations of FR II radio galaxies and quasars made for other purposes (e.g., Donahue et al 2003;. This has motivated us to collate all existing data on the hot spots of 3C radio sources from the Chandra archive and analyze them in a systematic way, with the aim of determining trends and testing models.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that X-ray inverse-Compton limits rule out such models in several individual cases (Hardcastle et al 1998;Croston et al 2003;Hardcastle & Croston 2010;Croston & Hardcastle 2014). For a subset of our FRI sample where the predicted levels are in principle detectable, we obtained upper limits on the lobe X-ray inverse-Compton emission, using the same method and assumptions as for the FRII inverseCompton measurements of I17.…”
Section: Samplementioning
confidence: 99%
“…We note that scenario (2) is already ruled out in some objects by X-ray inverse Compton limits (see Section 2.3); however, we wanted in this study to consider the population as a whole. For both scenarios the internal pressures are calculated using the SYNCH code of Hardcastle et al (1998), with the same electron energy distribution assumptions as for the FRII results of I17. The lobes are modelled as having uniform internal pressure.…”
Section: A Comparison Of Fri and Frii Pressure Ratiosmentioning
confidence: 99%
“…Previous nuclear observations of 3C 33 in the X-ray band date to those of the EINSTEIN observatory (Fabbiano et al 1984) and ROSAT (Hardcastle et al 1998;Hardcastle & Worrall 1999) X-ray telescopes. EINSTEIN only provided an upper limit to the 0.5−3 keV luminosity, while ROSAT/HRI could detect the source in the soft X-ray band, although the HRI instrument onboard was not able to resolve the source.…”
Section: Introductionmentioning
confidence: 99%